Effect of Supplementation of Thyme and Turmeric Essential Oils on Hemato-biochemical Parameters of Japanese Quails - Ranwa, Suman; Palod, Jyoti; Sharma, Rabendra K.; Kumar, Shive; Abhilasha (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This experiment was undertaken to assess the influence of thyme (Thymus vulgaris) and turmeric (Curcuma longa) essential oils on hematobiochemical parameters of Japanese quails. One hundred eighty, 6-day old Japanese quail chicks were subjected to five weeks trial. Quail chicks were distributed at random into five dietary treatment groups each with three replicates of 12 quails per treatment. Quails of T0 group fed diet without essential oils (Basal diet), T1 group fed basal diet with 0.2 % thyme essential oil, T2 group fed basal diet with 0.3% turmeric essential oil, T3 group fed basal diet with combination of 0.125 % thyme essential oil and 0.075 % turmeric essential oils, T4 group fed basal diet with combination of 0.075% thyme essential oil and 0.125 % turmeric essential oils. The results revealed that Japanese quails of essential oils supplemented groups had significantly higher (p<0.05) red blood cell count, packed cell volume, haemoglobin, mean corpuscular volume, mean corpuscular haemoglobin, serum protein, albumin globulin and high-density lipoprotein concentrations with best results found in T4 group. Supplementing Japanese quails with thyme and turmeric essential oils significantly lowered serum uric acid, creatinine, total bilirubin, glucose, total cholesterol, triglycerides, LDL, SGOT and SGPT activity. It can be concluded that nutritional supplementation of thyme and turmeric essential oils at 0.075 % and 0.125 % in combination improved haematological indices and most of the serum biochemical parameters in Japanese quails.